Improving Post-Earthquake Building Safety Evaluation using the 2015 Gorkha, Nepal, Earthquake Rapid Visual Damage Assessment Data. (December 2017) - Didier, Max; Baumberger, Salome; Tobler, Roman; Esposito, Simona; Ghosh, Siddhartha; Stojadinovic, Bozidar
A Rapid Visual Damage Assessment was initiated in the direct aftermath of the 2015 Gorkha earthquake to assess the safety and damage of residential buildings in the areas affected by the earthquake. Over 30, 000 paper assessment forms have been subsequently digitized. The collected data set allows comparison of the observed damage to the residential building stock to the damage expected using existing fragility curves. Under certain conditions and respecting certain limitations, the post-earthquake building safety and damage data can be used to update the existing fragility functions for the Nepalese building stock. Recommendations are made for the improvement of post-earthquake building safety assessments in Nepal in order to: (1) make data collection more consistent, (2) increase the accuracy of the collected data, and (3) make more effective use of the collected data after future earthquakes.